An event-driven simulation-optimisation approach to improve the resiliency of operation in a double-track urban rail line. Issue 5 (3rd September 2022) - Shahabi, Ali; Raissi, Sadigh; Khalili-Damghani, Kaveh; Rafei, Meysam
ABSTRACT: Urban rail transit often has high sensitivity against random disruptions. Hence regularity of the rail services should be maintained to prevent adverse impacts. This study focused on an objected-oriented discrete-event simulation platform to generate an efficient operation plan for such networks in the cases of degraded modes. The main goal is to generate an operation plan by taking into account the headway regularity index for a two-direction loop urban rail line under temporary line blockage disruptions. Accordingly, an optimized injection-withdrawal schedule proposed using a simulation-optimization approach enriched with Iterated Local Search heuristic method. The proposed method has the capability of quantifying the stochastic system resiliency. Real experiments derived from the 2nd line of the Karaj underground railway. Results revealed an improvement of 5.6% for the regularity index and 4.7% for the inbound and outbound routes, respectively.